Risk Factors for Macroscopic Haemoglobinuria After Sclerotherapy Using Ethanolamine Oleate for Venous Malformations. (July 2019) - Fujiki, Masahide; Ozaki, Mine; Kurachi, Isao; Iwashina, Yuki; Takushima, Akihiko
Abstract : Objectives: Sclerotherapy is an essential component of the treatment for venous malformations, and ethanolamine oleate (EO) is known as a useful sclerosing agent. However, macroscopic haemoglobinuria (MH) and subsequent renal impairment are severe complications after sclerotherapy using EO. The present study aimed to clarify the MH risk factors for better peri-operative management of venous malformations. Methods: Data collected during 130 procedures involving 94 patients who were undergoing sclerotherapy using EO for venous malformation were retrospectively analysed. Pre-operative and operative variables, including sex, age, pre-operative body mass index, location, depth, type of lesion, size, number of procedures, type of drainage vein, ratio of sclerosant to air, and injected total dose of 5% EO per body weight (BW), were examined. Univariable analysis and multivariable logistic regression were performed to determine the possible risk factors for MH. Results: Following sclerotherapy, MH occurred in 27.7% of patients, but no patient developed post-operative renal impairment because of aggressive hydration and haptoglobin administration. On univariable analysis, diffuse lesion, lesion size ≥50 cm 2, and total injected dose of 5% EO ≥ 0.18 mL/kg were found to be the MH risk factors. Multivariable logistic regression analysis identified a total injected dose of 5% EO ≥ 0.18 mL/kg as the significant independent factor contributing to MH risk. Conclusions: Macroscopic haemoglobinuria is a reversible complication if immediate and appropriate interventions with aggressive hydration and haptoglobin administration are performed; therefore, it should be closely monitored following sclerotherapy, especially when using 5% EO ≥ 0.18 mL/kg.